Bodies, Camera, Screen: Eiko & Koma’s Immersive Media Dances - Candelario, Rosemary (The International Journal of Screendance, 2014)
Eiko & Koma are New York-based Japanese American dance artists known for their subtle, focused, and finely controlled movement vocabulary through which they alter the perception of time and space. For over forty years they have created works for the proscenium stage, outdoor sites, galleries, and the camera that address elemental issues of life, survival, death, and rebirth. Their close and unsparing attention to nature, mourning, and human relationships to other humans and the world around them has won them prestigious awards including Guggenheim, MacArthur, and United States Artist Fellowships, Bessies, and Doris Duke Performing Arts Awards.